An adaptive hierarchical data dissemination mechanism for mobile data collector enabled dynamic wireless sensor network. (15th July 2021) - Mazumdar, Nabajyoti; Roy, Saugata; Nag, Amitava; Nandi, Sukumar
Abstract: Recent studies have revealed that the energy hole problem caused by multi-hop data collection in a static data collector based wireless sensor network(WSN) is a major threat to the lifetime of the network. With the advancement of mobile terminal technology, the application of mobile data collectors (MDCs) has gained popularity in a large scale WSN. A WSN design with one or more MDC can significantly diminish the energy hole problem, which in turn prolongs the network operational lifetime. However, most of the MDC based existing schemes suffer from achieving a balance between routing energy consumption and data delivery delay. Moreover, the majority of the sensor network protocols fail to retain their impact as the network topology changes due to the inclusion or exclusion of nodes. So, for a dynamic WSN, it is essential to support a recovery mechanism to continue the data propagation despite inevitable changes in the WSN topology. Considering all the aforementioned challenges, this paper proposes an adaptive hierarchical data dissemination (AHDD) mechanism for multiple MDC enabled dynamic wireless sensor network, which alleviates the energy hole problem as well as resolves the fault-tolerance issue. Simulation results demonstrate that the proposed protocol has shown improved performance with respect to performance metrics namely, network lifetime, energy efficiency, packet delivery percentage, and end-to-end delay.